ANALISIS PROFITABILITAS DENGAN MENGGUNAKAN ROA DAN ROE PADA PERUSAHAAN SEKTOR BASIC MATERIALS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022 : - - Radja, Firmike Lidyatami; Dwi Febrianti, Fitria (JURNAL EKONOMI PEMBANGUNAN, 2024)
The purpose of this research is to evaluate the financial performance of a company based on the return on total equity (ROE). The data used in this research are secondary data, which is obtained using documentation studies and library studies. The data analysis method is a quantitative descriptive method, by describing or describing the results of the data that has been collected and processed. The results can be used to evaluate whether the company has worked well. The company's management performance over a certain period can be evaluated using the measurement results. This research is carried out on companies that have gone public or that have been officially registered in the Indonesian capital market, in this case, the Indonesia Stock Exchange, especially on companies included in the basic materials sector for the period 2022